2005
DOI: 10.1111/j.1442-2042.2005.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of urinary nerve growth factor and prostaglandins in male patients with overactive bladder symptom

Abstract: Aim : Nerve growth factor (NGF) and prostaglandins (PG) in the urinary bladder can be affected by pathology of bladder, and this change can be noted in the urine. This study was performed to investigate the changes in urinary NGF and PG in male patient with overactive bladder (OAB) symptoms.Methods : The study group included 75 male patients with OAB symptoms and 20 males without bladder symptoms as controls. Evaluation included history-taking, urinalysis, International Prostate Symptom Score (IPSS) and urodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 20 publications
4
81
1
1
Order By: Relevance
“…High concentrations of PGE2 have been detected in the urine of OAB patients, suggesting that PGE2 may contribute to the pathophysiology of the disorder. 79,80 Prostanoids may affect afferent activity in two ways: by effects on the smooth muscle and/or via direct effects on afferent nerves. Prostaglandins have direct contractile effects on the human detrusor, which may contribute to the spontaneous contractile activity.…”
Section: Local Mediators Influencing Spontaneous Activitymentioning
confidence: 99%
“…High concentrations of PGE2 have been detected in the urine of OAB patients, suggesting that PGE2 may contribute to the pathophysiology of the disorder. 79,80 Prostanoids may affect afferent activity in two ways: by effects on the smooth muscle and/or via direct effects on afferent nerves. Prostaglandins have direct contractile effects on the human detrusor, which may contribute to the spontaneous contractile activity.…”
Section: Local Mediators Influencing Spontaneous Activitymentioning
confidence: 99%
“…Recent studies have demonstrated the presence of NGF in the urine of OAB patients (Kim et al, 2005;Kim et al, 2006;Liu & Kuo, 2008;Liu et al, 2009a, b;Liu et al, 2009c;Jacobs et al, 2010;Liu et al, 2011a). Levels were significantly higher than in healthy individuals and subsided after successful treatment with antimuscarinics (Liu et al, 2009b) or botulinum toxin-A (Liu et al, 2009a), in parallel with a decrease in the USS score.…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 99%
“…This supports a role for this prostanoid during bladder dysfunction and has justified a few inconclusive clinical trials regarding the use of non-steroidal anti-inflammatory drugs in the treatment of OAB. So, expectations were raised when Kim and co-workers found that levels of PGE 2 and PGF 2 were significantly higher in male and female OAB patients that in healthy controls (Kim et al, 2005;Kim et al, 2006). However, PG concentrations were not corrected for urine concentration.…”
Section: Prostaglandinsmentioning
confidence: 99%
“…These results suggest that increased Ngf is associated with clinical BPH symptoms. 16 In order to determine if NGF also plays a role in abnormal prostate growth, we examined the effects of innervation on NGF abundance and localization in sham, denervated and intact (contralateral) ventral prostate (VP) after pelvic ganglionectomy. We propose that denervation on one side of the VP increases prostate innervation and autonomic hyperactivity in the contralateral non-perturbed VP, which may result in increased growth.…”
Section: Introductionmentioning
confidence: 99%